Validity of the Brazilian version of WHOQOL-BREF in depressed patients using Rasch modelling - Neusa Sica da Rocha (Revista de Saúde Pública, 2009)
OBJECTIVE: To assess the validity of the Brazilian version of the World Health Organization Quality of Life Instrument – Abbreviated version (WHOQOLBREF) in adults with major depression, using Rasch modelling. METHODS: Study analyzing data from the baseline sample of the Longitudinal Investigation of Depression Outcomes in Brazil, including a total of 208 patients with major depression recruited in a primary care service in Porto Alegre (Southern Brazil), in 1999. The Center for Epidemiological Studies Depression Scale was used to assess intensity of depression; the WHOQOLBREF to assess generic quality of life; and the Composite International Diagnostic Interview version 2.1 for the diagnosis of depression. RESULTS: In the Rasch analysis, the four domains of WHOQOL-BREF showed appropriate fi t to this model. Some items needed adjustments: four items were rescored (pain, fi nances, services, and transport); two items (work and activity) were identifi ed as having dependency of responses, and one item was deleted (sleep) due to multidimensionality. CONCLUSIONS: The validation of the WHOQOL-BREF Brazilian version using Rasch analysis complements previous validation studies, evidencing the robustness of this instrument as a generic cross-cultural quality of life measure.